Characteristics of Solid Waste Agar Industries - Ifah Munifah; Hari Eko Irianto (Research and Development Center for Marine and Fisheries Product Processing and Biotechnol, 2018)
Agar processed from red seaweed Gracilaria sp. in Indonesia can be found in the form of sheet and powder. The abundance of cellulose in agar solid waste can be used as an alternative source of carbon for microorganism growth. The purpose of this study was to determine the component of agar solid waste and to characterize the cellulose. The agar solid waste (limbah industri agar-agar, LIA) was undergone physical separation process into agar, fiber cellulose, and celite. The result showed that agar solid waste consisted of 53.53% fiber; 37.33% agar and 8.60% celite. LIA was characterized for its components including ash, lignin, extractive substances, cellulose, hemicellulose, and holocellulose using Technical Association of the Pulp and Paper Industry Method (TAPPI). The TAPPI analysis revealed that solid waste generated from seaweed Gracilaria sp processing had 28.19% cellulose, 38.83% holocellulosa, 10.63% hemicellulose, 8.27% ash, 3.54% insoluble acid ash, 11.23% water, and 1.62% extractives substances. The lignin content of the solid waste was low (2.08%), therefore it has potential to be utilized as biomass (bio fertilizer, alternative carbon source). The components in solid waste of agar was determined using Fourier Transform Infra Red (FTIR). The LIA sample had high content of celite indicated by the absorption peak which appears at wave length 2343.45 cm-1 for the -Si-H bond and at the wave length 772.99 cm-1 for the bond -Si- O-. Infra-red spectra showed that celite still exist in solid waste of agar. The study indicated that there was still a large amount of cellulose in the solid waste of agar. Keywords: solid waste, cellulose, agar, lignin, celite